Circumstantial risk: Impact of future tax evasion and labor supply opportunities on risk exposure - Philipp Doerrenberg; Denvil Duncan; Christopher Zeppenfeld (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
This paper examines whether risk-taking in a lottery depends on the opportunity to respond to the lottery outcome through additional labor effort and/or tax evasion. Previous empirical attempts to answer this question face identification issues due to self selection into jobs that facilitate tax evasion and labor effort exibility. We address these identification issues using a laboratory experiment (N = 180). Subjects have the opportunity to invest earned income in a lottery and, depending on randomly assigned treatment states, have the opportunity to respond to the lottery outcome through evasion and/or extra labor effort. We find strong evidence that ex-post access to labor opportunities reduces ex-ante risk willingness while access to tax evasion has no effect on risk behavior. We discuss possible explanations for this result based on the existing literature.
urn:nbn:de:bsz:180-madoc-359482
Keywords: G11; H21; H24; H26; J22; 330; Tax Evasion; Labor Supply; Risk Behavior; Lab Experiment